Gli esordi di Carla Cerati fotografa, 1960-1964 - Sorrentino, Cristiana (Rivista di studi di fotografia. Journal of Studies in Photography, 2019)
This paper investigates the first period of Carla Cerati’s (1926-2016) photographic career, focusing in particular on three main issues: her beginnings as a member of the Circolo Fotografico Milanese in the early 1960s; the critical reception and primary interpretations of her work during the same period; and the analysis of her photographic language, based on the first reconstruction of her initial output.